Desarrollo y estandarización de un ELISA indirecto para la detección de anticuerpos contra el Herpesvirus bovino tipo 1 - Valera, Alejandro Rafael (1999)
An indirect enzyme linked immunosorbent assay (I-ELISA) was developed to detect antibodies to BHV-1 in serum samples. Nonidet P40-solubilized infected with BHV-I reference strain and mock-infected cell lysates were used as antigens. Serum samples were diluted 1: 64 and a commercial horse radish peroxidase-labelled rabbit anti-bovine lgG was used as second antibody. The reaction was developed using azino-dietilbenzotiazol-sulfonate (ABTS). Cut-off was determined by ratio sample (Rs). Virus neutralization (VN) test was used as a reference test over the 587 samples, 416 of them were positive by VN and 1-EL1SA, 145 were negative by both techniques, and 26 were positive by 1-EL1SA and negative by VN. Using VN as standard, the ELISA showed a relative specificity and sensibility of 100 and 84.79%, respectively.